Digital Didactics Embedded in Ethnomathematics Assessment of Online Mathematics Instruction - Ali, Clement Ayarebilla (Universitas Negeri Semarang, 2024)
Online and e-learning programmes have shifted the power bloc to the learner within their cultural settings. In a case study-based qualitative design, the researchers sampled 40 student-teachers to produce and laminate works of prominent women scientists’ contributions. The data was collected through observations and unstructured interviews. The items were coded on four 7-point Likert scales to represent the planning and design (satisfaction), teaching and learning (reflection), as and through learning (priority), formative assessment (quality), and assessment of virtual class (satisfaction). In qualitative content analysis, the medians predominantly pooled 6 while the modes pooled between 5 and 8 (multimodal). In cases where the median was greater than the mode, we had positive skewness and the reverse was negative skewness. The Spearman’s correlation coefficients showed that only one pair recorded strong positive correlation and two to three pairs recorded strong negative correlations. The chi-square tests for independence showed the null hypothesis was rejected to mean that there were associations among the variables. It was concluded that digital didactics was the central point for the design and use of teaching and learning. It was therefore concluded that digital didactics innovated mathematics instruction and learning.